Answer:
Step-by-step explanation:
Since 2 of the 3 binomials are identical I would start the distribution there.
(1 + 4i)(1 + 4i) = ![1+8i+16i^2](https://tex.z-dn.net/?f=1%2B8i%2B16i%5E2)
I'm sure you have learned in class by now that i-squared is = to -1, so we can make that substitution:
1 + 8i + 16(-1) which simpifies to
1 + 8i - 16 which simplifies further to
-15 + 8i. Now we need to FOIL in the last binomial:
(-15 + 8i)(-4 + 4i) = ![60-60i-32i+32i^2](https://tex.z-dn.net/?f=60-60i-32i%2B32i%5E2)
Combine like terms to get
![60-92i+32i^2](https://tex.z-dn.net/?f=60-92i%2B32i%5E2)
Again make the substitution of i-squared = -1:
60 - 92i + 32(-1) which simplifies to
60 - 92i - 32 which simpifies, finally, to a solution of:
28 - 92i
Answer:
-2
Step-by-step explanation:
7-3/2-4=-2
use slope formula
Alright, so [-2.99] is -2.99, and [2.99] is 2.99, so -2.99+2.99=0
If r = 1/6 and 1/6 is next to 12, it's multiplication. so that's 12 x 1/6.
12 x 1/6 = 2 i believe.
X + y = 54
x - y = 34
----------------add
2x = 88
x = 88/2
x = 44
x + y = 54
44 + y = 54
y = 54 - 44
y = 10
so ur 2 numbers are 44 and 10